Turkey's Alevi Enigma : A Comprehensive Overview - Jongerden, Joost; White, Paul J. (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
This volume discusses how the multifaceted reality of Turkey's Alevis impinges on society and politics in contemporary Turkey. The book provides readers with a vigorous discussion of the origins and history of the Alevis, examines their ethnic identity and cultural representation, as well as appraising their political life and the effect that this had on Turkey's polity, the Turkish Left and the Kurdish National Movement, and upon the emergence of civil society. It analyses Alevi cultural manifestations and even looks at how Alevi diaspora communities in Europe effect Turkey in various ways. The book therefore provides readers with a convenient handbook of an important group that is largely unknown in the West - Turkey's Alevis.